1976
DOI: 10.1021/bi00666a005
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the thermal pretransition of synthetic phospholipids: dimyristoyl- and dipalmitoyllecithin

Abstract: The hydrated synthetic lecithins, dimyristoyl and dipalmitoyllecithins, undergo two thermal transitions, a broad low enthalpy "pretransition" prior to the sharp first-order "chain-melting" transition. Both phospholipids exhibit the same temperature-dependent structural changes associated with the thermal pretransition. At low temperatures, below the pretransition, a one-dimensional lamellar lattice is observed. The hydrocarbon chains are fully extended and tilted with respect to the plane of the lipid bilayer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

84
509
7
5

Year Published

1978
1978
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 975 publications
(605 citation statements)
references
References 22 publications
84
509
7
5
Order By: Relevance
“…3b), the values of t p & 11-13°C and t m & 23-24°C being in good agreement with data from the literature (Cevc 1993;Janiak et al 1976). In the fluid phase at 33°C, d = 6.26 nm, similar to 6.27 nm at 30°C reported by Nagle and TristramNagle (2000).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…3b), the values of t p & 11-13°C and t m & 23-24°C being in good agreement with data from the literature (Cevc 1993;Janiak et al 1976). In the fluid phase at 33°C, d = 6.26 nm, similar to 6.27 nm at 30°C reported by Nagle and TristramNagle (2000).…”
Section: Resultssupporting
confidence: 88%
“…In the disordered fluid L d phase, the repeat distance diminishes slowly. This temperature dependence of d is typical of DPPC in excess water (Janiak et al 1976;Tenchov et al 1989). At 50°C, d = 6.77 nm, a value similar to that (6.70 nm) mentioned by Nagle and TristramNagle (2000).…”
Section: Resultsmentioning
confidence: 80%
“…The assumption that neutral lipids are miscible with phospholipids is consistent with the fact that cholesteryl esters can be dispersed in either monolayer [6][7][8][9] or bulk phospholipid systems [10][11][12][13]. Smaby et al [7] demonstrated that cholesteryl oleate and dioleoylphosphatidylcholine form stable monolayers with a solubility limit of 43 tool% for the cholesteryl ester.…”
Section: Introductionmentioning
confidence: 79%
“…Smaby et al [7] demonstrated that cholesteryl oleate and dioleoylphosphatidylcholine form stable monolayers with a solubility limit of 43 tool% for the cholesteryl ester. According to Janiak et al [11], a bulk lipid system of hydrated dimyristoylphosphatidylcholine accommodates less cholesteryl ester; the ternary system was completely miscible to approx. 5 mol% of cholesteryl myristate.…”
Section: Introductionmentioning
confidence: 99%
“…It is established that DPPC bilayers undergo two thermal transitions above room temperature (24). One is a low-enthalpy pretransition and the other is a high-enthalpy chain melting transition (29). Below the pretransition temperature, DPPC forms a two-dimension lamellar structure in which the hydrocarbon chains are fully extended in an all-trans conformation and tilted with respect to the plane of the bilayer.…”
Section: Discussionmentioning
confidence: 99%